2017
DOI: 10.23865/hu.v7.905
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to learning as predictors of academic achievement: Results from a large scale, multi-level analysis

Abstract: The relationships between university students' academic achievement and their approaches to learning and studying continuously attract scholarly attention. We report the results of an analysis in which multilevel linear modelling was used to analyse data from 3,626 Danish university students. Controlling for the effects of age, gender, and progression, we found that the students' end-of-semester grade point averages were related negatively to a surface approach and positively to organised effort. Interestingly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
1
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 36 publications
3
18
1
8
Order By: Relevance
“…The surface approach scale score was associated with GPA only among the Norwegian students. In this instance, lower surface approach scores predicted higher GPA, which is in agreement with previous findings (Herrmann et al, 2017;Richardson et al, 2012;Salamonson et al, 2013;Zeegers, 2001). However, it is apparent from this crosscultural study that the theoretically anticipated associations between the ASSIST scales and academic performance are not always confirmed empirically in diverse samples and settings.…”
Section: Associations Between Assist Scale Scores and Gpasupporting
confidence: 93%
See 2 more Smart Citations
“…The surface approach scale score was associated with GPA only among the Norwegian students. In this instance, lower surface approach scores predicted higher GPA, which is in agreement with previous findings (Herrmann et al, 2017;Richardson et al, 2012;Salamonson et al, 2013;Zeegers, 2001). However, it is apparent from this crosscultural study that the theoretically anticipated associations between the ASSIST scales and academic performance are not always confirmed empirically in diverse samples and settings.…”
Section: Associations Between Assist Scale Scores and Gpasupporting
confidence: 93%
“…However, it was the strongest predictor of higher GPA among the students from Norway and Hong Kong (see Table 3). The results from the analysis of the Norwegian and Hong Kong students are in line with previously reported research, which similarly emphasized the strategic approach to studying as a means to achieving good academic outcomes (Diseth & Martinsen, 2003;Herrmann, McCune, & Bager-Elsborg, 2017;Richardson et al, 2012). In contrast, for the students from Australia (and for the total sample), spending more time on self-study was associated with higher GPA results (see Table 3).…”
Section: Associations Between Assist Scale Scores and Gpasupporting
confidence: 87%
See 1 more Smart Citation
“…However, associations appear consistently weak. Moreover, some studies have indicated that a deep approach to learning is unrelated to academic achievement (Karagiannopoulou and Milienos, 2015;Herrmann et al, 2017). The most consistent positive association is between academic achievement and the strategic approach/organized study (Duff, 2003;Diseth et al, 2010;Rytkönen et al, 2012;Milienos, 2013, 2015;Asikainen et al, 2014).…”
Section: Research In Approaches To Learningmentioning
confidence: 99%
“…Also, approaches to learning have been found to have an effect on achievement although the findings are inconsistent (Herrmann et al, 2017). Deep, strategic and surface approaches have been positively and negatively associated, respectively, with academic achievement and study success (Richardson et al, 2012;Haarala-Muhonen et al, 2017;Herrmann et al, 2017;Entwistle, 2018).…”
Section: Research In Approaches To Learningmentioning
confidence: 99%